2018
DOI: 10.1590/1983-1447.2018.20170229
|View full text |Cite
|
Sign up to set email alerts
|

Comunicação em saúde por meio do ambiente virtual: relato de experiência

Abstract: Resumo OBJETIVO relatar a experiência da estratégia de comunicação em saúde por meio de hospedagem de vídeos de saúde em um ambiente virtual. MÉTODO relato de experiência com educação em saúde por hospedagem de vídeos nos temas reanimação cardiopulmonar, obstrução da via aérea por corpos estranhos e hemorragias, utilizando páginas da internet (site) de compartilhamento de vídeos (YouTube), páginas acessíveis na internet (websites) e ferramentas para melhorarem tarefas (aplicativos). RESULTADOS em dezessete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
(6 reference statements)
0
1
0
2
Order By: Relevance
“…Finally, the current ease of disseminating videos over the internet expands the reach of lay people who are willing to learn about cardiopulmonary resuscitation. Researchers ( 25 ) identified that educational videos made available on virtual platforms reached more than thirty thousand people, including Brazilians and foreigners, demonstrating, once again, its potential in health education for laypeople. In another investigation, the authors ( 26 ) show that after the SARS-CoV-2 virus pandemic, there was a relevant increase in the search for online health training on the various video and videoconference platforms.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the current ease of disseminating videos over the internet expands the reach of lay people who are willing to learn about cardiopulmonary resuscitation. Researchers ( 25 ) identified that educational videos made available on virtual platforms reached more than thirty thousand people, including Brazilians and foreigners, demonstrating, once again, its potential in health education for laypeople. In another investigation, the authors ( 26 ) show that after the SARS-CoV-2 virus pandemic, there was a relevant increase in the search for online health training on the various video and videoconference platforms.…”
Section: Discussionmentioning
confidence: 99%
“…De acordo com Libardi (2018), esse modelo de atualização funciona como uma extensão do ambiente acadêmico, que procura uma interação dialógica com a comunidade, complementando e aprofundando o conhecimento científico. Outro ponto importante é a comodidade que esse tipo de atualização oferece.…”
Section: Discussionunclassified
“…Devido à sua versatilidade, os vídeos são promissores como uma estratégia de educação em saúde, por serem interativos e de fácil acesso, levando a uma grande aceitação do público 9 . Esse tipo de tecnologia educacional permite que o indivíduo aprenda por si próprio e complemente seu conhecimento no seu próprio tempo 10 , diante da liberdade de reproduzir, pausar e retroceder sempre que considerar necessário para atender às suas necessidades de aprendizagem 11 .…”
Section: /13unclassified